2006
DOI: 10.1007/s00167-006-0057-2
|View full text |Cite
|
Sign up to set email alerts
|

New intraoperative protocol for kinematic evaluation of ACL reconstruction: preliminary results

Abstract: A real improvement in anterior cruciate ligament (ACL) surgery would be achieved if a global kinematic evaluation of graft performance could be made during surgery. A quantitative evaluation of all residual instabilities would be helpful in the evaluation of graft performances. This paper describes a new protocol for an accurate and extensive computer-assisted in vivo evaluation of joint laxities during ACL reconstruction. Fifteen in vivo kinematic evaluations during ACL reconstruction were performed using an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 27 publications
1
50
0
1
Order By: Relevance
“…Specifically, all kinematic measurements were taken by a single surgeon using one type of CR implant and surgical technique, and furthermore, inter-rater reliability was not measured. However, several in vivo studies have shown a high inter-rater reliability for knee kinematic measurements using a navigation system [3,9,28]. Thus, we consider that our kinematic data allow valid comparisons of the kinematics of preoperative and postoperative conditions in the same knees.…”
Section: Discussionmentioning
confidence: 83%
“…Specifically, all kinematic measurements were taken by a single surgeon using one type of CR implant and surgical technique, and furthermore, inter-rater reliability was not measured. However, several in vivo studies have shown a high inter-rater reliability for knee kinematic measurements using a navigation system [3,9,28]. Thus, we consider that our kinematic data allow valid comparisons of the kinematics of preoperative and postoperative conditions in the same knees.…”
Section: Discussionmentioning
confidence: 83%
“…The surgeon first located the hip joint center by circumducting the femur and used a probe to acquire anatomical landmarks (femoral epicondyles, tibial malleoli, and tibial plateau extremities), which were used to compute femoral and tibial reference systems and obtain relative motion data based on the Grood and Suntay algorithm. [28][29][30] After acquiring the landmarks, knee flexion angle and the relative orientation between femur and tibia were displayed in real-time for use in the kinematic evaluation. Kinematic tests included the following manuevers: varus/valgus (VV) stress at 0 and 308 at maximum load and passive ROM from maximum extension to maximum flexion.…”
Section: Methodsmentioning
confidence: 99%
“…They have been integral in increasing our understanding of knee kinematics, improving diagnostic capabilities, and stimulating the development of non-invasive devices for quantifying knee laxity in the clinical setting. Despite their efficacy, navigation systems are often invasive, complex, and expensive [26][27][28][29]. Moreover, they cannot be employed in the clinical setting and are typically reserved for intra-operative analysis.…”
Section: Resultsmentioning
confidence: 99%